Evidence of complex formation between alkaline phosphatase and a pro-apoptotic hemoprotein cytochrome c - Dadák, V; Janda, P; Janiczek, O (General physiology and biophysics, 1999)
Two proteins, alkaline phosphatase (AP) and cytochrome c (cyt c) which seem to be involved in the apoptotic cell death program were examined on their interaction. Intestinal AP affects ferricytochrome c (cyt c(FeIII)) by changing its optical properties, redox state and conformation. The effect proceeded over the course of hours with a gradual decrease in free cyt c(FeIII) as the AP concentration increased. A heme containing high molecular species was created in the first stage of interaction of the proteins in neutral, acidic (pH 2.6), alkaline (pH 8.3), low ionic strength (10 mmol/l phosphate), and high ionic strength (0.5 mol/l NaCl) media. Further complexation was favored by higher pH values and temperature. Differential scanning calorimetry revealed a decrease in enthalpy of the thermodenaturation temperature (Tm) of cyt c at 84.5 degrees C due to the AP addition. Increments of AP in the mixtures resulted in the appearance of Tm peaks at 68 degrees C and 61 degrees C. Electrophoretic analysis of the commercial samples of intestinal APs showed main fractions from 63.2 kDa to 72.9 kDa and from 172.9 up to 179.0 kDa. Changes in positions and intensities of the bands were detected upon longer incubation (24 h) with cyt c. The electrophoretic pattern of the bacterial AP was homogeneous with one fraction of 43.7 kDa showing no alteration due to the cyt c presence. Gel permeation chromatography of incubated mixtures of intestinal APs and cyt c confirmed the creation of new heme containing complexes.
Keywords: koncentrace vodíkových iontů; cytochromy skupiny c; Spectrophotometry, Ultraviolet; gelová chromatografie; Chromatography, Gel; denaturace proteinů; alkalická fosfatasa; Hydrogen-Ion Concentration; vazba proteinů; apoptóza; diferenciální skenovací kalorimetrie; Apoptosis; Alkaline Phosphatase; Cytochrome c Group; Protein Denaturation; Calorimetry, Differential Scanning; spektrofotometrie ultrafialová; Protein Binding; Electrophoresis, Polyacrylamide Gel; elektroforéza v polyakrylamidovém gelu